MODERN ASPECTS OF STATE STRATEGIC PLANNING AND STATE POLICY IN UKRAINE - Usachenko , Oleksandr (Theory and Practice of Public Administration, 2019)
Strategies identified through strategic planning are guidelines for action through the development of public policies based on them. The strategic planning of socio-economic development, municipal management was investigated in the works of Galchinsky, A.S., Heyets, V.M., Sharova, Yu.P.; methodological aspects of state policy in Ukraine were investigated: Walewski, O. L., Rebkalo, V.A., Tertychka, V.V.; Public policy analyzes were undertaken by Deepak C. Gupta and Andrew, C. and Hugue Hecklo and many other researchers. The paper objective is the definition of modern aspects of state strategic planning and state policy in Ukraine. The development of modern state management strategies, first of all, is aimed at solving two main tasks: firstly, long-term significant improvement of the state of its management object (sphere, industry, region, territory, relations) by providing appropriate state management, and, according to – the second, long-term significant improvement of the state of its subject of governance (the system or individual higher, central or local government bodies, civil service, etc.) through self-organization. At the same time, in the process of strategic planning, the strengths and weaknesses, the threats and benefits that are achieved using the SWOT analysis method should be highlighted. The most well-known documents adopted at the highest level of the public administration system are: annual messages from the Presidents of Ukraine to the Verkhovna Rada of Ukraine; strategies of economic and social development of Ukraine; programs of activity of the Cabinet of Ministers of Ukraine. The latter, in fact, were adopted after each change of government. They were adopted in the form of programs of government’s top-priority measures until strategic planning was initiated. That is, these programs until the appearance at the end of 1999 of signs of Ukraine’s exit from the economic crisis, along with the messages of the President of Ukraine, served as the main documents that set the benchmarks for overcoming the target disorganization for the current year. The article defines the principle approach for state strategic planning and state policies, the purpose, the main tasks of the strategic documents that have been developed in Ukraine for the past 20 years. The comparative characteristic of strategic planning in the countries of the European Union and other developed countries is made. According to the results of the analysis, a number of problem issues related to the implementation of state policy in Ukraine have been identified, in particular: there is currently no document such as a direct action law or a clear instruction on the development and implementation of state policy, there is a documentation gap from the needs of society and a formal declaration, as well repeating the situation for many years.